Python fundamentals : a practical guide for learning Python, complete with real-world projects for you to explore ([Packt Publishing], 2018)
"After a brief history of Python and key differences between Python 2 and Python 3, you'll understand how Python has been used in applications such as YouTube and Google App Engine. As you work with the language, you'll learn about control statements, delve into controlling program flow and gradually work on more structured programs via functions. As you settle into the Python ecosystem, you'll learn about data structures and study ways to correctly store and represent information. By working through specific examples, you'll learn how Python implements object-oriented programming (OOP) concepts of abstraction, encapsulation of data, inheritance, and polymorphism. You'll be given an overview of how imports, modules, and packages work in Python, how you can handle errors to prevent apps from crashing, as well as file manipulation. By the end of this course, you'll have built up an impressive portfolio of projects and armed yourself with the skills you need to tackle Python projects in the real world."--Resource description page